The effect of corporate social responsibility practices on brand equity: An examination of malaysia's top 100 brands - Zahari A.R.; Esa E.; Rajadurai J.; Azizan N.A.; Tamyez P.F.M. (Korea Distribution Science Association (KODISA), 2023)
The study aims to provide some evidence of the effects of CSR practices on financial-based brand equity in Malaysia. Nowadays, many companies have embraced corporate social responsibility (CSR) practices because CSR is a vital component of the current competitive and complex business arena. It contributes greatly to social, environmental, and economic condition. With CSR practices, companies are able to achieve many benefits and there is evidence that CSR practices predict higher brand equity. However, little evidence has been produced concerning the effects of CSR practices on financial aspects of brand equity in developing countries such as Malaysia. Therefore, this paper aims to investigate the effects of CSR practices on financial based brand equity among Malaysia Top 100 brand. A CSR checklist instrument was used in the current study to examine the extent of CSR practiced. The results indicated that PLCs that were actively involved in CSR practices such as environmental, community, workplace and marketplace, found that this involvement enhanced their brand equity. The findings provide useful support and evidence for the management of PLCs in Malaysia, as well as companies in other developing countries, to engage more in CSR practices as a core element of their strategic and brand management. Korean Distribution Science Association (KODISA).